Efficacy of Purple Chrysanthemum Ethanol Extract in Inhibiting Staphylococcus aureus and Escherichia coli Growth - Paukiran, Degol; Budiarso, Fona; Manampiring, Aaltje; Fatimawali, Fatimawali; Bodhi , Widdhi; Kepel, Billy Johnson (Grimsa Journal of Science Engineering and Technology, 2025)
Staphylococcus aureus, a Gram-positive bacterium, and Escherichia coli, a Gram-negative bacterium, are known to cause both enteric and systemic infections in humans. The improper use of antibiotics has often been associated with the emergence of antibiotic resistance. Purple chrysanthemum (Chrysanthemum morifolium) has shown significant potential as an alternative treatment, owing to its strong antioxidant, anti-inflammatory, and antibacterial properties. These properties are attributed to the presence of bioactive compounds such as polyphenols, flavones, essential oils, and other phytochemicals. This study aimed to identify secondary metabolites and evaluate the antibacterial activity of ethanol extracts from purple chrysanthemum (Chrysanthemum morifolium). The extraction process was conducted using Ultrasonic-Assisted Extraction (UAE), and the antibacterial activity was assessed using the disc diffusion method at extract concentrations of 12.5%, 25%, and 50%, with ciprofloxacin serving as the positive control. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, phenolics, and steroids in the ethanol extract of purple chrysanthemum. Importantly, all ethanol extracts demonstrated antibacterial activity. The highest inhibition zones were observed at a 50% concentration, with S. aureus showing an inhibition zone of 12.35 ± 0.4 mm, while E. coli exhibited an inhibition zone of 15.08 ± 0.22 mm.